(untitled)
The French philosopher of contemporary science, Gaston Bachelard, has clearly and accurately expressed the nature of the dialectical relationship between science and method by saying: When science changes its methods, it becomes more systematic. And a method of analyzing scientific knowledge. For this reason, we see Bachelard and in most of his works confirm that the main tasks of epistemology are to carry out a psychological analysis of objective knowledge Bachelard has tried hard to clarify the basic picture that links epistemology to psychoanalysis, by searching for basic concepts such as the concept of epistemological obstacle and the concept of epistemological rupture and epistemological obstacle, from which epistemological analysis benefits from psychoanalysis and which helps him analyze scientific knowledge.